Optimalisasi Pendidikan Keagamaan dan Literasi Al-Qur’an pada Santri Pondok Pesantren Al-Fahd, Banyuasin, Sumatera Selatan - Anisa Yuhadi; Rahma Aliya; Sonia Sonia; Mesi Angraini; Ep Riadi; Henny Yusalia (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
This study aims to analyze the optimization of religious education and Qur’anic literacy among students at Al-Fahd Islamic Boarding School, Jakabaring, Palembang City, through the implementation of integrative educational service programs during Community Service Program activities. The implemented programs included Qur’anic literacy assistance using the Haramain method, habituation of hadith culture, strengthening daily sunnah practices, hadith memorization development, contextual English learning, mathematics mentoring using finger-counting techniques, unit conversion ladder learning, educational hadith media, and digital literacy through Ramadan content creation. This study employed a descriptive qualitative approach using observation, documentation, direct participation, and field reflection. The findings indicate that the optimization of religious and academic education improved students’ Qur’anic reading quality, strengthened hadith understanding and Islamic moral habituation, increased learning motivation, and enhanced numeracy and English communication skills. Furthermore, practical and media-based learning integration created more active, enjoyable, and contextual educational experiences. The study concludes that collaborative approaches integrating religious values and academic learning can effectively improve the quality of Islamic boarding school education.